Analisis Tanggung Jawab Lingkungan, Sosial dan Tata Kelola Perusahaan Terhadap Nilai Perusahaan, Kinerja Keuangan dan Laba Perusahaan - Aghry Ghoriyyudin; Harry Z. Soeratin (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Government-regulated Corporate Social Responsibility (CSR) programs are intended to reduce the impact on society and the environment, but CSR cannot be done without the support of good corporate governance (GCG). The purpose of this study is to ascertain and examine previous research on the impact of corporate governance and environmental and social responsibility, or CSR, on corporate value, financial performance, and profits. This research combines qualitative methods with a literature study strategy, which involves using data collected from publications published in national journals to support ideas. Twenty samples of indexed and non-indexed articles were selected by the researchers from Google Scholar. Based on the findings of previous research studies, this study found that the impact of corporate governance (GCG) and corporate social responsibility (CSR) on financial performance and firm value varies. By increasing stakeholder trust, CSR often improves profitability, however, these benefits are not always visible due to high implementation costs. The contribution of corporate governance, including audit committees and independent boards, to business efficiency and transparency varies. Researchers believe that a more thorough study of the impact of GCG and CSR on firm value, financial performance, and profits will be conducted in the future.